Effect of altitude on soil physico-chemical properties and microbial biomass carbon in the Eaglenest Wildlife Sanctuary of Arunachal Pradesh - Genius Teron; Reetashree Bordoloi; Ashish Paul; Lal Bihari Singha; Om Prakash Tripathi (Geology, Ecology, and Landscapes)
The present study focuses on the variation in soil properties and microbial biomass carbon along an elevation gradient in the Eaglenest Wildlife Sanctuary, Arunachal Pradesh. Soil was acidic in nature and pH value ranges from 4.37 ± 0.14 to 5.25 ± 0.29. Soil texture varied from sandy to loamy sand. Clay content and available potassium showed a significant negative correlation (p < 0.05) with altitude. Water holding capacity and available nitrogen showed a strongly significant positive correlation (p < 0.01). Soil bulk density, temperature, moisture content, pH, available phosphorus and microbial biomass carbon showed a strongly significant negative correlation (p < 0.01) with altitude. Soil organic carbon stock was highest (66.39 ± 9.36 t h−1) in tropical zone and lowest (44.33 ± 6.34 t h−1) in temperate zone. Higher soil organic carbon and organic matter (4.16 ± 0.58% and 7.17 ± 1.00%) were found in subtropical zone while lowest (2.57 ± 0.38% and 4.42 ± 0.64%) were found in tropical zone. Available nitrogen and available potassium were highest (604.10 ± 24.13 kg h−1 and 418.14 ± 26.53 kg h−1) in subtropical zone and lowest available potassium (282.82 kg h−1 ± 14.68 kg h−1) was recorded in the temperate zone. Higher available phosphorous (62.51 ± 6.96 kg h−1) was recorded in tropical zone while lowest (10.66 ± 1.49 kg h−1) was recorded in the subtropical zone. The first four main components of the principal component analysis jointly explained 78.51% of the overall variation. The results from the principal component analysis align closely with Pearson’s correlation analysis and analysis of variance, reinforcing the accuracy and reliability of the observed trends in data. The present study clearly indicates that altitudinal variation exerts a significant effect on the soil’s physico-chemical properties. It suggests that understanding the effects of altitudinal variation on soil properties is important for the establishment and restoration of the vegetation in diverse altitudinal zone.